Mechanism of persistent heavy PM2.5 pollution over the Beijing-Tianjin-Hebei region of China: A combination of aerosol radiative effect and atmospheric quasi-biweekly oscillation. (15th June 2023) - Gao, Libo; Wang, Tijian; Ren, Xuejuan; Ma, Danyang; Qu, Yawei; Wu, Hao
Abstract: The persistent heavy PM2.5 pollution (PHP) occurs frequently over the Beijing-Tianjin-Hebei (BTH) region in winter, but the formation mechanism is not fully understood. Using a regional climate-chemistry-ecology model RegCM-Chem-YIBs, we investigated the synergetic impacts of aerosol radiative effect (ARE) and atmospheric quasi-biweekly oscillation (QBWO) on a PHP event in December 2013. The event consists of two peak stages and a persistence stage between them. Process analysis shows that chemical reactions and advection are the most important processes in the accumulation of PM2.5 . Chemical reactions contribute 30–40 μg m −3 hr −1 to the rapid development of PHP, which is far more than that in clean days. Through sensitivity experiments, the influences of ARE and QBWO on PM2.5 variation via changing meteorological conditions were quantified respectively. During the event, ARE leads to a reduction of 24.0% in solar radiation and −33.8% in surface air temperature. The planetary boundary layer height is lowered by 20.8%. The feedback of ARE to PM2.5 ranges from 20 to 170 μg m −3, with the largest changes at PM2.5 peak stages. In comparison, QBWO exerts dominant influence at the persistence stage, during which the East Asia trough and northerlies are weakened constantly. Besides, QBWO causes a decrease of −39.5% in wind speed and an increase of 14.3% in relative humidity near the surface. The rates of chemical process and advection are increased considerably at the first peak stage and the persistence stage. QBWO also slows down the dissipation of PHP, prolonging the pollution duration. Finally, a range of 60–110 μg m −3 increase in PM2.5 is attributed to QBWO. In all, ARE and QBWO take different roles in the formation of PHP. ARE mainly affects the pollution intensity by accelerating chemical reactions, while QBWO determines the persistence of heavy pollution by changing both advection and chemical processes. Graphical abstract: Image 1 Highlights: PHP results from the cooperation of atmospheric quasi-biweekly oscillation (QBWO) and aerosol radiative effect (ARE). QBWO favors local accumulation and chemical formation at the persistence stage, prolonging the pollution duration. ARE accelerates the chemical reactions at peak stages, reinforcing the pollution intensity.